Social Problems and Threats of Digital Technologies Based on Artificial Intelligence - Vassiliy Sherstyuk; Elena Mitskaya; Muh. Afif Mahfud (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2026)
The problems of interaction between humans and digital technologies based on artificial intelligence cannot be regarded as resolved. The aim of this study is, through the generalisation of various viewpoints on the interaction between humans and artificial intelligence, to find an answer to the question of whether the digital revolution represents another, albeit radical, improvement in human life, one that may nevertheless displace humans from the pinnacle of evolution, or whether it constitutes something that is destined to replace humans altogether. The following methods were employed: logical analysis, observation, sociocultural analysis, synthesis, comparison, induction, forecasting, and generalisation. The results obtained indicate that three key problems in the interaction between humans and artificial intelligence have been identified. First, there is a declining human capacity to control digital technologies due to their revolutionary development. Second, there is an incorrect assessment of, or even a complete disregard for, the negative consequences of the total digitalisation of all spheres of life. Third, humans tend to overestimate their ability to control digital technologies based on artificial intelligence. In order to ensure further interaction between humans and the artificial intelligence they have created, the study proposes measures aimed at counteracting the criminalisation of artificial intelligence.